Forms of Discrimination against Woman in Selected Iraqi Proverbs: A Critical Discourse Analysis - Badr , Lecturer. Huda Hadi (Thi Qar Arts Journal, 2022)
The present study investigates discrimination against a woman in the light of critical discourse analysis (CDA) in selected Iraqi proverbs, specifically those used in Baghdad and Basra. It aims to find out the ideological themes implied in the said proverbs about a woman. The  significance of this study is to show the different forms of discrimination against a woman in the these proverbs. The proverbs indicating forms of discrimination against a woman are collected from three important reference books, namely, Aldileeshy(1968), Al-Hanafi (1962), Al-Hanafi (1964) in addition to some proverbs taken from Al-Zubaidi (2019). The proverbs selected for this study are analyzed according to their interpretation in the reference books in which they occur. Moreover, these proverbs are selected on the basis that they seem to have not been tackled from the perspective of CDA. Furthermore, to detect the ideological themes implied in the aforementioned proverbs, a qualitative approach is used. In addition, thirty four proverbs are selected and only nine examples are analyzed to reveal the sexist ideologies whether in the structure or the structure and the function of the previously mentioned proverbs. The findings reached at in the present study include the following forms of discrimination against a woman: hating the birth of a girl child, vilifying a woman, violating her, discriminating against her in terms of gender affinity, marital status and beauty, woman inferiority to a man and undervaluing a woman's work. Additionally, most of the proverbs selected convey discriminatory concepts against a woman through the structure and the function whereas a few of them convey such concepts through the structure only. Further, only one proverb referring to discrimination against a woman through the function occurs.